miR-150-5p suppresses tumor progression by targeting VEGFA in colorectal cancer - Chen, Xiaoxiang (Aging (Albany NY), 2018)
MicroRNA-150-5p (miR-150-5p) has been implicated in tumor initiation and progression in a variety of cancers. However, its roles in colorectal cancer (CRC) remain largely unknown. In our study, a decreased miR-150-5p expression in CRC tissues was found to be associated with poor overall survival. Moreover, miR-150-5p inhibited CRC cell proliferation, migration, invasion and angiogenesis in vitro and in vivo, and its inhibitory effect could be reversed by transfection of vascular epithelial growth factor A (VEGFA) expression plasmid. Lastly, we demonstrated that miR-150-5p inactivated VEGFA/VEGFR2 and the downstream Akt/mTOR signaling pathway in CRC. Based on these results, we conclude that miR-150-5p may function as a tumor suppressor in CRC, and miR-150-5p/VEGFA axis may be a potential therapeutic target candidate in CRC treatment.